2016
DOI: 10.1111/bjh.14437
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary and clinical implications of the uneven distribution of the frequency of the inherited haemoglobin variants over short geographical distances

Abstract: SummaryStudies of the frequency of heterozygous carriers for common inherited diseases of haemoglobin in over 7500 adolescent children in 25 districts in Sri Lanka have disclosed a highly significant variation over very short geographical distances. A further analysis of these findings, including their relationship to the past frequency and distribution of malaria, climatic variation, altitude, ethnic origin and consanguinity rates, have provided evidence regarding the evolutionary basis for the variable distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 20 publications
0
36
1
Order By: Relevance
“…However, a recent survey showed a high (8.0%) prevalence of -thalassaemia trait [7]. Surprisingly, -thalassaemia is more prevalent than betathalassaemia and IDA in many parts of the country (Table 1) [7]. In contrast to what was previously described, this data suggests, that haemoglobinopathy rather than ID is the likely cause of anaemia in a significant proportion of children.…”
Section:     -Thalassaemiacontrasting
confidence: 60%
See 2 more Smart Citations
“…However, a recent survey showed a high (8.0%) prevalence of -thalassaemia trait [7]. Surprisingly, -thalassaemia is more prevalent than betathalassaemia and IDA in many parts of the country (Table 1) [7]. In contrast to what was previously described, this data suggests, that haemoglobinopathy rather than ID is the likely cause of anaemia in a significant proportion of children.…”
Section:     -Thalassaemiacontrasting
confidence: 60%
“…This is due to the rarity of clinically significant -thalassaemia (haemoglobin H disease and Barts hydrops foetalis) in Sri Lanka and to technical difficulties in confirming -thalassaemia trait which is only feasible through DNA analysis. However, a recent survey showed a high (8.0%) prevalence of -thalassaemia trait [7]. Surprisingly, -thalassaemia is more prevalent than betathalassaemia and IDA in many parts of the country (Table 1) [7].…”
Section:     -Thalassaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The National prevalence of β-thalassaemia trait is reported as 2.8% and the prevalence in the Galle District where this study was conducted 1.0%. Contrarily to previous believes, a recent island wide survey by Premawardhana et al reported that the prevalence of α-thalassaemia trait is as high as 8.0% in Sri Lanka and that it is found in every district including Galle [2]. As reviewed by us previously, α-thalassaemia is commoner than β-thalassaemia and may in fact be as common as iron deficiency anaemia [3].…”
Section: S Mettanandamentioning
confidence: 84%
“…, DGH de Silva 2 We read with interest the article by Senadheera et al, which describe the rate of anaemia and iron deficiency in women presenting for antenatal care in a Teaching Hospital in the Galle District of Sri Lanka [1]. We agree with the content on the rate of anaemia defined as haemoglobin concentration <11g/dl however, the subsequent analysis to determine a cut-off level of serum ferritin for detection of anaemia is inaccurate.…”
Section: S Mettanandamentioning
confidence: 85%